2020
DOI: 10.1155/2020/1038636
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Compounds from Vietnamese Piper bavinum

Abstract: This study reports the anti-inflammatory activity-guided fractionation of the aerial part of Piper bavinum C. CD. (Piperaceae) that led to the isolation of eight secondary metabolites (1–8). The chemical structures of 1–8 were established mainly by NMR and mass spectra. Compound 5 was isolated from P. bavinum for the first time. All the isolated compounds were evaluated against LPS-induced NO production in macrophage RAW 264.7 cells in vitro. Among them, compound 4 showed the most potent inhibitory activity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…From our results, the flavonoid (+)-catechin (2) strongest inhibited NO production (4.8 ± 0.2 μM), followed by (−)-epicatechin (3) exhibited inhibitory effects with an IC50 value of 5.7 ± 0.5 μM, presumably because of the presence of the 3,4-hydroxylation(s) in the benzene ring (Figure 1) and this result is similar to those of previously reported [22][23][24]. Meanwhile, the inhibitory activities on NO production of compounds 4 and 5 were significantly reduced (IC50 values of 18.4 ± 1.2 and 9.6 ± 0.8 μM, respectively) and compound 1 was inactive, presumably because of the lack of 3-hydroxylation (compounds 1 and 4) of the benzene ring or the presence of the methoxy groups (compound 5) in benzene ring (Figure 1) [22][23][24][37][38][39]. These results suggested that flavan-3-ol bearing the 3,4-hydroxylation of the benzene ring could be considered as new lead compounds for the development of agents against NO production.…”
Section: Figure 2 Effect On Cell Viability Compounds 1−5supporting
confidence: 49%
“…From our results, the flavonoid (+)-catechin (2) strongest inhibited NO production (4.8 ± 0.2 μM), followed by (−)-epicatechin (3) exhibited inhibitory effects with an IC50 value of 5.7 ± 0.5 μM, presumably because of the presence of the 3,4-hydroxylation(s) in the benzene ring (Figure 1) and this result is similar to those of previously reported [22][23][24]. Meanwhile, the inhibitory activities on NO production of compounds 4 and 5 were significantly reduced (IC50 values of 18.4 ± 1.2 and 9.6 ± 0.8 μM, respectively) and compound 1 was inactive, presumably because of the lack of 3-hydroxylation (compounds 1 and 4) of the benzene ring or the presence of the methoxy groups (compound 5) in benzene ring (Figure 1) [22][23][24][37][38][39]. These results suggested that flavan-3-ol bearing the 3,4-hydroxylation of the benzene ring could be considered as new lead compounds for the development of agents against NO production.…”
Section: Figure 2 Effect On Cell Viability Compounds 1−5supporting
confidence: 49%
“…The NMR data of 2 showed good similarity with those of trans ‐phytol. [ 14 ] Therefore, 2 was indicated as trans ‐phytol.…”
Section: Resultsmentioning
confidence: 99%
“…By chromatography methods, including column chromatography and thin layer chromatography, seven compounds were isolated from the methanolic extract of M. calabura leaves. They were 5-(δtocopherol-5'-yl)-δ-tocopherol (1), [13] trans-phytol (2), [14] ergosta-4,6,8 (14),22-tetraen-3-one (3), [15] ergosterol peroxide (4), [16] stigmasta-4-ene-3,6-dione (5), [17,18] 6-hydroxystigmast-4-en-3-one (6), [19] and β-sitosterol (7) (figure 1). [20] This is the first time that compounds 1-6 have been reported for Muntingia genus.…”
Section: Resultsmentioning
confidence: 99%